1998
DOI: 10.1152/jn.1998.80.1.92
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Neuronal Migration Disorders in Neocortical Structures. II. Intracellular In Vitro Recordings

Abstract: Neuronal migration disorders (NMD) are involved in a variety of different developmental disturbances and in therapy-resistant epilepsy. The cellular mechanisms underlying the pronounced hyperexcitability in dysplastic cortex are not well understood and demand further clinical and experimental analyses. We used a focal freeze-lesion model in cerebral cortex of newborn rats to study the functional consequences of NMD. Intracellular recordings from supragranular regular spiking cells in cortical slices from adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
80
2
1

Year Published

1999
1999
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(93 citation statements)
references
References 75 publications
10
80
2
1
Order By: Relevance
“…There was some evidence for an increased activation in the unaffected, contralateral hemisphere, as postulated from the in vitro experiments (Chevassus-au-Louis et al, 1999;Jacobs et al, 1996;Luhmann and Raabe, 1996;Luhmann et al, 1998b). Still, the dominant findings of our study were (1) absence of obvious neurologic deficits, and (2) highly reduced activation (fMRI and SSEPs) in the lesioned hemisphere.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…There was some evidence for an increased activation in the unaffected, contralateral hemisphere, as postulated from the in vitro experiments (Chevassus-au-Louis et al, 1999;Jacobs et al, 1996;Luhmann and Raabe, 1996;Luhmann et al, 1998b). Still, the dominant findings of our study were (1) absence of obvious neurologic deficits, and (2) highly reduced activation (fMRI and SSEPs) in the lesioned hemisphere.…”
Section: Discussionsupporting
confidence: 55%
“…Although the amount of tissue is reduced as well, previous in vitro slice studies revealed enhanced rather than decreased excitability of the malformed cortex and the surrounding tissue (Jacobs et al, 1996;Luhmann and Raabe, 1996;Luhmann et al, 1998b). Therefore, reasons other than mere tissue loss must account for the reduced activation found in the present study.…”
Section: Loss Of Excitable Tissuementioning
confidence: 39%
See 1 more Smart Citation
“…The development of the neural system involves a series of time and space dependent events, being related to the date of birth of the neurons and their interaction with the radial glia (Wilsnack et al, 1984;Chevassus-Au-Louis et al, 1998;Luhmann et al, 1998;Redecker et al, 1998;VelezDomingues, 1998;Aversi-Ferreira et al, 2004;AversiFerreira et al, 2005;Aversi-Ferreira et al, 2006, AversiFerreira & Nascimento, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…В связи с этим выделяют расстройства нейрональной миграции -врожденные структурные ано-малии развития головного мозга, а также признаки синап-тической регенерации [69]. Эти данные указывают, что шизофреноподобный психоз при эпилепсии может быть связан как с де-, так и регенеративными изменениями в мозге, которые могут быть результатом нарушения разви-тия ЦНС или генетического дефекта [70].…”
unclassified